Risk-based e-business testing - Gerrard, Paul (Artech House computing library., 2002)
This hands-on guide for business, project and test managers and test practitioners presents an effective approach for using risk to construct test strategies for e-business systems. Using an easily-learned risk-analysis technique, it teaches you how to use risk to select and prioritize test methods for e-business projects. This innovative resource shows you how to select test techniques to address business risks and integrate them into a coherent test process.